Evaluation of Black Bengal breeding buck based on sexual urge, semen quality and non-return rate: Evaluation of Black Bengal breeding buck (Bangladesh Journal of Animal Science, 2026)
This study was carried out to evaluate the sexual urge, semen quality, and non-return rate (NRR) of Black Bengal breeding bucks to establish criteria for selecting superior bucks. Data were collected from five bucks aged between 17 and 19 months over a period of five months. The results showed that, reaction time (RT) and erection status (ES) differed significantly among the bucks (p0.05) differences were observed for libido and fixing strength (FS). Moreover, significant difference (p